A Research Gap in Large-Project Financial Management (International Journal of Innovative Research in Engineering & Management, 2021)
This article discusses financial management research in  major projects published in publications with high influence.  Our objective is to discover answers to the following  questions from the study: (a) what financial features are being  studied? (b) Financial concepts for big project management?  The approach utilised was a bibliographical analytic of  research articles produced between 2000 and 2013 in the  major databases. Our findings show that success is the most  prominent element, despite the fact that there is still no  agreement on performance evaluation. Whereas in recent  years there has been a rise in the quantity of papers in this  field, there is also the absence of high-impact journals.  Example studies (almost 60%), with only one case covered in  most situations, and are the most often utilised approach.  Financial efficiency is the most frequently studied topic; however, no consensus has yet been reached on how to assess  megaproject performance. A megaproject evaluation is rarely  carried out, even though it is the financial objective of any  company. Fiscal research and analyses of the key  programmes' financial framework are likewise scarce. Such  similar research areas of focus include stakeholder or risk  management, as well as public-private partnerships.
Keywords: Financial; Management; Megaprojects; Projects; Risk; Social